Localized nuclear and perinuclear Ca2+ signals in intact mouse skeletal muscle fibers - Georgiev, Tihomir; Svirin, Mikhail; Jaimovich, Enrique; Fink, Rainer (Frontiers in physiology, 2015)
Nuclear Ca2+ is important for the regulation of several nuclear processes such as gene expression. Localized Ca2+ signals (LCSs) in skeletal muscle fibers of mice have been mainly studied as Ca2+ release events from the sarcoplasmic reticulum. Their location with regard to cell nuclei has not been investigated. Our study is based on the hypothesis that LCSs associated with nuclei are present in skeletal muscle fibers of adult mice. Therefore we carried out experiments addressing this question and we found novel Ca2+ signals associated with nuclei of skeletal muscle fibers (with possibly attached satellite cells). We measured localized nuclear and perinuclear Ca2+ signals (NLCSs and PLCSs) alongside cytosolic localized Ca2+ signals (CLCSs) during a hypertonic treatment. We also observed NLCSs under isotonic conditions. The NLCSs and PLCSs are Ca2+ signals in the range of micrometer (FWHM (full width at half maximum): 2.75 µm±0.27 µm (NLCSs) and 2.55 µm±0.17 µm (PLCSs), S.E.M.). Additionally, global nuclear Ca2+ signals (NGCSs) were observed. To investigate which type of Ca2+ channels contribute to the Ca2+ signals associated with nuclei in skeletal muscle fibers, we performed measurements with the RyR blocker dantrolene, the DHPR blocker nifedipine or the IP3R blocker Xestospongin C. We observed Ca2+ signals associated with nuclei in the presence of each blocker. Nifedipine and dantrolene had an inhibitory effect on the fraction of fibers with PLCSs. The situation for the fraction of fibers with NLCSs is more complex indicating that RyR is less important for the generation of NLCSs compared to the generation of PLCSs. The fraction of fibers with NLCSs and PLCSs is not reduced in the presence of Xestospongin C. The localized perinuclear and intranuclear Ca2+ signals may be a powerful tool for the cell to regulate adaptive processes as gene expression. The intranuclear Ca2+ signals may be particularly interesting in this respect.